Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1073/pnas.1100120108
|View full text |Cite
|
Sign up to set email alerts
|

Apolar surface area determines the efficiency of translocon-mediated membrane-protein integration into the endoplasmic reticulum

Abstract: Integral membrane proteins are integrated cotranslationally into the membrane of the endoplasmic reticulum in a process mediated by the Sec61 translocon. Transmembrane α-helices in a translocating polypeptide chain gain access to the surrounding membrane through a lateral gate in the wall of the translocon channel [van den Berg B, et al. (2004) To clarify the nature of the membrane-integration process, we have measured the insertion efficiency into the endoplasmic reticulum membrane of model hydrophobic segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 37 publications
(43 reference statements)
5
60
4
Order By: Relevance
“…2B). These stepwise reductions in ΔG app are larger than the value obtained previously for linear aliphatic side chains (−0.26 kcal/mol per carbon) (3). Subtracting the aliphatic contribution, we find that the ΔΔG app for moving the charged guanidinium group one methyl group (∼1.2 Å) closer to the membrane interface varies, as shown in Fig.…”
Section: Resultsmentioning
confidence: 38%
“…2B). These stepwise reductions in ΔG app are larger than the value obtained previously for linear aliphatic side chains (−0.26 kcal/mol per carbon) (3). Subtracting the aliphatic contribution, we find that the ΔΔG app for moving the charged guanidinium group one methyl group (∼1.2 Å) closer to the membrane interface varies, as shown in Fig.…”
Section: Resultsmentioning
confidence: 38%
“…Perhaps more likely, the Bam complex might lower the free energy of membrane insertion, but the efficiency of insertion is ultimately dictated by the biophysical properties of each substrate. Indeed a recent study showed that although the Sec machinery greatly enhances the partitioning of α-helical transmembrane segments into a lipid bilayer, insertion efficiency is influenced by the nonpolar surface area of individual amino acid side chains (37). Moreover, although the generality of our results remains to be determined, it is noteworthy that the mutation of a conserved glycine residue in the β domain of a trimeric autotransporter also appears to affect its membrane insertion (38).…”
Section: Discussionmentioning
confidence: 63%
“…Öjemalm et al (22) found that the apparent translocon-to-membrane free energy of insertion of nonproteinogenic amino acids at a particular position in the TM segment varied linearly with σ, as expected for hydrophobic-driven partitioning. However, σ was found to be less favorable than that for bulk water/hydrocarbon partitioning and to depend on position within the model TM segment (Fig.…”
mentioning
confidence: 99%